Performance-related payments in local governments: do they improve performance or only increase salary? - Spano, Alessandro; Monfardini, Patrizio (2018)
Personnel policies in public sector organizations are fundamental to improving public services, since they have an impact on both individual and organizational performance. Within the broad area of Human Resources Management (HRM), Performance-Related Pay Systems (PRPSs) are widely considered one of the cornerstones of public sector managerial reforms. Monetary incentives should be paid for performance achievements of single employees and/or teams, according to a defined set of objectives. While the role and appropriateness of PRPSs in the public sector have been widely discussed in the literature, in some countries monetary incentives have been used as a tool to increase individual salaries, without considering them as a motivating instrument in a wider HRM system. A small number of studies have been conducted to understand the limitations of this form of incentives and to investigate whether it can be replaced by different and more effective incentives in order to avoid the de-motivating effect caused by money, as recognized in the literature. This study tries to fill this gap investigating, through twenty-five interviews to informed respondents the effectiveness of existing PRPSs at Local government level in Italy both in terms of performance and motivation and the possibility to substitute monetary with non-monetary incentives. The findings suggest that the limitations of monetary incentives have been widely recognized, but it is still difficult to replace them with different and more effective alternatives. - Reproduced.
Keywords: Local government; Performance evaluation; Service rating